Pengaruh Produksi Karet, Kurs Dollar Amerika Serikat, dan Ekspor Karet Terhadap Cadangan Devisa Indonesia Periode 1995-2012 - Kurniawan, Ketut Edo; Bendesa, I Komang Gede (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 3, No. 7, Juli 2014 (pp.282-336), 2014)
Rubber is one of Indonesia's largest export commodity. Export activities bring many benefits to the people of Indonesia, one of which is a natural outcome Indonesian market. Through interstate commerce enabled Indonesian exporters sell goods abroad. This transaction could increase foreign exchange. Thus the country's wealth will increase due to foreign exchange is one source of state revenue. This study aims to determine whether there is influence or partially simultaneously the most dominant variable affecting the Indonesian foreign exchange reserves, between rubber production, the U.S. dollar exchange rate and export of rubber. To solve the problem of multiple linear analytical technique used to test the circuit is: classical assumption test, F test and t test. Based on the results o data processing, it is known that rubber export variables significant influence Indonesia's foreign reserves, while the production of rubber and the U.S. dollar exchange rate did not significant influence the foreign exchange reserves of Indonesia from 1995 to 2012.
Keywords: Foreign Exchange Reserves, Production of Rubber , Rubber Exchange and Export